Application of hydrolytic enzymes and refining on recycled fibers - Maximino, Mirta Graciela (2011)
The present study analyses the effects of the enzymatic treatment with Pergalase A40 (a blend of cellulases and hemicellulases) on an industrially recycled pulp made up of old corrugated container (OCC) fibers, kraft liners and a low percentage of white office paper. The enzymatic treatment was carried out through a 2³ experimental design, by varying pulp concentration, enzyme dosage and treatment time. Furthermore, a combined treatment (enzyme plus PFI mechanical refining) was also evaluated, to obtain a greater improvement in drainability, while maintaining or improving the properties of secondary fibers. Enzymatic pre-treatment of recycled fibers without refining increases the initial freeness degree of pulp, practically without any loss in tensile strength, for most of the conditions analyzed. Generally, combined treatments (enzyme + refining) show that a higher tensile index level may be attained, with significant drainability improvement and minor specific energy consumption – comparatively with the reference pulp.